WOOD-BASED MARKET IN RIO GRANDE DO NORTE BETWEEN 1999 AND 2019 - Silva, Luciélia Lacerda da; Guimarães, Pompeu Paes; Castro, Vinícius Gomes de; Carmo, Flavio Cipriano de Assis do; Quirino, Natália Isabel Lopes; Nobrega, Edyla Maria Alves (Floresta, 2023)
The objective of this work was to analyze the firewood, charcoal and roundwood market in the state of Rio Grande do Norte (RN) in the period 1999-2019. Data provided by the Brazilian Institute of Geography and Statistics (IBGE) were used referring to the quantity produced, unit value (UV) and gross production value (GPV), subdivided according to Agreste, Central, East and West mesoregions in RN. These variables were simplified in the form of descriptive statistics, with the UV and GPV deflated with a base year of 1999. In addition, the exploration products, the total area explored, the type of cut and the situation regarding the plans of sustainable forest management - PMFS, were analyzed, as provided by the Northeastern Plant Information Center (Centro Nordestino de Informações Sobre Plantas, CNIP). The results generated allowed us note that the West mesoregion stood out in the production of firewood, being the second largest producer of charcoal and the only producer of roundwood logs. The highest UV per ton of coal occurred in 2016 in the Agreste and West mesoregions; in 2018, in the Central mesoregion and, in 2013, in the East. The highest UV per cubic meter of firewood occurred in 2017 for the Agreste and Central regions, and in 2019, in the East and West mesoregions, respectively. The Central mesoregion had the highest number of PMFS in the state, with most of the plans that are currently active being used for the exploitation of firewood. West mesoregion presented only two assets.